Conceptual Points for Consideration by the Oxnard Airport Authority Pertaining to the Future of Oxnard Airport and the Draft Revised Master Plan and EA/EIR - Richard J. Maggio:::::: (1999)
Correspondence discussing points which were identified in a meeting with the Oxnard Airport Authority.